Фінансування інноваційного сектору економіки - Халатур, Світлана Миколаївна; Khalatur, Svitlana (Хмельницький національний університет, 2024)
Інноваційний сектор економіки відіграє вирішальну роль у стимулюванні економічного зростання, підвищенні конкурентоспроможності та забезпеченні сталого розвитку держави. Однак ключовим викликом є пошук і залучення достатніх фінансових ресурсів для підтримки інноваційних процесів. У статті досліджено основні джерела та механізми фінансування інновацій, аналізується сучасний стан інноваційної діяльності, а також розглядаються перспективи розвитку та вдосконалення фінансової інфраструктури для підтримки інноваційного сектору економіки. Financing the innovative sector of the economy is a topical topic for research, as innovation is a key factor in ensuring sustainable economic development in the face of globalization and a rapidly changing market environment. In connection with technological shifts, changes in consumer preferences and productivity requirements, innovation financing has become an important component of enterprise development strategy. The innovative sector of the economy covers a wide range of activities, including scientific research, development of new products, technologies and services, as well as improvement of existing processes. In the context of financing innovation, a variety of funding sources must be considered, which may include government grants, private investment, venture capital, crowdfunding, and other mechanisms. Effective financing of innovations should contribute not only to the development of specific projects, but also to ensuring the competitiveness of the national economy as a whole. The availability of sufficient financial resources is critical for the implementation of innovative ideas and the introduction of new technologies, which, in turn, can increase productivity, reduce costs and contribute to the growth of the population's well-being. Modern economic conditions require the adaptation of approaches to financing innovations, which involves the study of both internal and external factors affecting the availability and effectiveness of financial resources. In this context, the study of the problems of financing the innovative sector of the economy is not only a scientific, but also a practical task that requires a comprehensive approach and interdisciplinary analysis. The innovation sector of the economy plays a crucial role in stimulating economic growth, increasing competitiveness and ensuring sustainable development of the state. However, the key challenge is to find and attract sufficient financial resources to support innovation processes. The article examines the main sources and mechanisms of financing innovations, analyses the current state of innovation activity, and considers the prospects for the development and improvement of financial infrastructure to support the innovation sector of the economy
Financing of the innovation sector of the economy
Keywords: інновації; innovation; глобалізація; globalisation; венчурний капітал; venture capital; техноглобалізм; technoglobalism; технології; technology; інноваційний розвиток; innovative development; нанотехнології; nanotechnology; глобальний ринок; global market; промислові революції; industrial revolutions; економічне зростання; economic growth